Evaluation of novel enzyme blend on nursery pig performance - DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Two experiments were conducted to determine the effects of a dietary enzyme blend and diet complexity on weanling pig performance. In Exp. 1, 180 pigs (initially 12.7 lb BW and 21 d of age) were used in an 18-d growth trial. Pigs were blocked by weight and randomly allotted to 1 of 3 dietary treatments with 5 pigs per pen and 12 pens per treatment. The 3 dietary treatments included (1) a high-complexity positive control, (2) a low-complexity negative control, and (3) a treatment with an added proprietary enzyme blend (Engrain LLC, Manhattan, KS). All diets were fed in 2 phases, with pigs fed a Phase 1 pelleted diet from d 0 to 8 and a Phase 2 diet in meal form from d 9 to 18. From d 0 to 8, pigs fed the high-complexity diet had improved (P < 0.05) ADG and F/G compared with pigs fed the low-complexity diet without enzymes. Also, pigs fed the low-complexity diet with enzymes tended to have increased (P < 0.10) ADG and improved (P < 0.05) F/G compared with pigs fed the low-complexity diet without enzymes. From d 9 to 18, no differences were observed in growth among pigs fed any of the dietary treatments. Overall (d 0 to 18), pigs fed the high-complexity diet had improved (P < 0.05) F/G compared with pigs fed the low-complexity diet with or without enzymes, but ADG and ADFI did not differ among the 3 dietary treatments.
Keywords: Swine; Diet complexity; Enzyme; Nursery pig